Development of a fluorescent nanoprobe based on an amphiphilic single-benzene-based fluorophore for lipid droplet detection and its practical applications. Issue 27 (27th June 2022) - Jung, Yuna; Jin, Ji Hye; Kim, Youngseo; Oh, Ji Hyeon; Moon, Heechang; Jeong, Huisu; Kim, Jaehoon; Park, Yoon Kyung; Oh, Yohan; Park, Sungnam; Kim, Dokyoung
Abstract : A new fluorescent nanoprobe based on a single-benzene-based fluorophore is developed for the detection and bioimaging of lipid droplets and applied in the visualization of fingerprints. Abstract : Lipid droplets (LDs) are crucial biological organelles connected with metabolic pathways in biological systems and diseases. To monitor the locations and accumulation of LDs in lipid-related diseases, the development of a visualization tool for LDs has gained importance. In particular, LD visualization using fluorescent probes has gained attention. Herein, a new fluorescent nanoprobe, BMeS-Ali, is developed that can sense LDs based on an amphiphilic single benzene-based fluorophore (SBBF). BMeS-Ali consists of hydrophilic (–NH2 ) and hydrophobic (–C12 H25 ) moieties and exists as a micelle nanostructure in aqueous media. BMeS-Ali has a weak fluorescence, but its emission was dramatically enhanced upon exposure to the LD components such as oleic acids (OA) by reassembling its nano-formulation. BMeS-Ali showed a selective LD staining ability and great biocompatibility in cells (cancer cells and stem cells). It also showed a practical sensing ability towards biologically derived lipids and can be applied to the visualization of human fingerprints. We found that the nanoprobe BMeS-Ali has significant potential to serve as a practical dye and sensor for lipids, especially for LD imaging in the biomedical research area and broader industrial applications.